2014
DOI: 10.1093/mp/ssu047
|View full text |Cite
|
Sign up to set email alerts
|

The Rice Restorer Rf4 for Wild-Abortive Cytoplasmic Male Sterility Encodes a Mitochondrial-Localized PPR Protein that Functions in Reduction of WA352 Transcripts

Abstract: Ahmadikhah, A., and karlov, G.I. (2006). Molecular mapping of the fertility-restoration gene Rf4 for WA-cytoplasmic male sterility in rice. Plant Breeding. 125, 363-367.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
104
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(110 citation statements)
references
References 7 publications
5
104
0
1
Order By: Relevance
“…2B). Notably, the RF6 protein contained a duplication of motifs 3-5, which are absent in rf6 or other known RF proteins (18,(33)(34)(35)(36)(37)(38) (Fig. 2B and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2B). Notably, the RF6 protein contained a duplication of motifs 3-5, which are absent in rf6 or other known RF proteins (18,(33)(34)(35)(36)(37)(38) (Fig. 2B and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As orf356, orf367 and WA314 have structures similar to WA352a and WA352c, we analyzed whether they also have CMS function. We prepared three binary constructs with MTS-orf356 (MTS, mitochondrial transit sequence), MTS-orf367, and MTS-WA314 ( Figure 2A) and transferred them into a CMS-WA maintainer line ZS97B with normal cytoplasm and the recessive restorer genes rf3 and rf4-i, an indica type rf4 allele [11]. The MTS fusion localizes the protein to mitochondria, thus allowing the test of CMS function using nuclear transformation [10,20].…”
Section: Functional Test Of the Candidate Cms Genesmentioning
confidence: 99%
“…japonica) Nipponbare (Nip) with the recessive rf3 and rf4-j (japonica type rf4), because that the expression of the genes is not affected in the absence of the functional restorer genes [10,11]. Quantitative reverse transcription PCR (qRT-PCR) showed that WA352b, WA352c, WA314, orf367, and orf356 were expressed in various tissues (root, stem, leaf, panicle, and anthers) of the corresponding backcrossing lines (shown in Supplementary information, Figure S3) or Nip (for orf284 and orf314 expression) ( Figure 3).…”
Section: Functional Test Of the Candidate Cms Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several rice Rf genes have been cloned: Rf1 (Rf1a, Rf1b) from Boro II type CMS (BT-CMS) rice (Kazama & Toriyama, 2003;Wang et al, 2006); Rf17 from Chinese wild CMS (CW-CMS) rice (Fujii & Toriyama, 2009); Rf2 from Lead type CMS (LD-CMS) (Itabashi et al, 2011); and Rf5 from HL-CMS rice . Rf3 from wild abortive-CMS (WA-CMS) and Rf6 from HL-CMS have also been mapped and Rf4 from WA-CMS was cloned Tang et al, 2014). A large mitochondrial complex ranging in size from 443 to 669 kDa and containing PPR592, pcf RNA and other factors was first reported in petunia (Gillman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%